2018
DOI: 10.1007/s10072-018-3475-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimating dementia cases in the immigrant population living in Italy

Abstract: Our findings indicate that the occurrence of dementia among immigrants and ethnic minorities constitutes a novel but already relevant issue for our healthcare systems. A non-negligible number of immigrant individuals is probably already seeking or might seek help for cognitive disturbances, thus potentially referring to general practitioners and/or to the Italian dementia services. The forecasted increasing magnitude of this phenomenon reinforces the need for tailored and locally oriented initiatives and polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Dementia is a syndrome of symptoms that affect cognition, memory, language and learning. It also often results in losing knowledge of the last language learned, and the person with dementia reverts to their native language [14]. This may have a negative effect on the ability to communicate one's needs.…”
Section: Introductionmentioning
confidence: 99%
“…Dementia is a syndrome of symptoms that affect cognition, memory, language and learning. It also often results in losing knowledge of the last language learned, and the person with dementia reverts to their native language [14]. This may have a negative effect on the ability to communicate one's needs.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that the epidemiology of dementia and parkinsonism varies across ethnic and immigrant groups [25][26][27][28][29][30] . A systematic review reported higher dementia incidence rates in the USA for Blacks and Caribbean Hispanic populations than other ethnic groups 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For Parkinson's disease, Van Den Eeden et al reported lower incidence rates for Asians and Blacks than Hispanics and non-Hispanic Whites in the USA 26 , although this could be related to care disparities as Blacks tend to present with more severe disease 31 . There is also considerable burden of neurodegenerative conditions among immigrants in Italy, Norway, the Netherlands, and the UK [27][28][29][30] . Parlevliet et al reported that dementia was three to four times more prevalent in most non-Western immigrant groups compared to the native Dutch population 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the issue of dementia among migrants in Italy has recently been estimated by applying dementia prevalence rates to the migrant population residing in the country. Nearly 7700 dementia cases were estimated in these individuals (5022 among women, 2725 among men), with a marked inter-regional variability 18. Among them, 1065 cases were calculated in the Lazio region.…”
Section: Introductionmentioning
confidence: 99%